RP-HPLC Estimation of Desloratadine in Pharmaceutical Dosage Form - VALARMATHY, J.; SAMUEL JOSHUA, L.; GUPTHA, N.T.H.; GANESH, M.; LAKSHMANA RAO, A.; SIVA KUMAR, T. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive and precise HPLC method has been developed for the estimation of desloratadine in pharmaceutical dosage form. In this method RP-C18 column (250 mm × 4.6 mm i.d., 5 μm particle size) with mobile phase consisting of acetonitrile, 0.05 M phosphate buffer and methanol in the ratio of 48:45:7 v/v/v in isocratic mode was used. The detection wavelength is 247 nm and the flow rate is 0.8 mL/min. In the range of 20-100 μg/mL, the linearity of desloratadine shows a correlation coefficient of 0.998. The percentage recovery ranges from 99.98-100.30 %. The proposed method was validated by determining sensitivity, accuracy, precision and linearity.